2013
DOI: 10.1128/aem.03512-12
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm as an Environment for Dissemination of stx Genes by Transduction

Abstract: Dissemination of Shiga toxin (Stx)-encoding bacteriophages is the most likely mechanism for the spread of Stx-encoding genes and the emergence of new Stx-producing Escherichia coli (STEC). Biofilm has been reported to be a place where horizontal gene transfer by plasmid conjugation and DNA transformation may occur, and in this study, horizontal gene transfer by transduction has been demonstrated. Transfer of Stx-encoding bacteriophages to potentially pathogenic E. coli in biofilm was observed at both 20°C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…The lysogens in our experiments were selected by antibiotics to facilitate the detection on the agar plates, and lower frequencies would probably be obtained without selection, but it should be noted that the lysogenization step in liquid culture was conducted without any antibiotic selection (see Materials and Methods). Our assays, which were conducted under laboratory conditions, may or may not be the most optimal for lysogenization, since transduction under "in vivo" conditions seems to be very effective (25,26,28,29). The Stx phage induced from the Norwegian O103:H25 isolate was shown to be capable of lysogeny after storage in a dry-fermented sausage model (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lysogens in our experiments were selected by antibiotics to facilitate the detection on the agar plates, and lower frequencies would probably be obtained without selection, but it should be noted that the lysogenization step in liquid culture was conducted without any antibiotic selection (see Materials and Methods). Our assays, which were conducted under laboratory conditions, may or may not be the most optimal for lysogenization, since transduction under "in vivo" conditions seems to be very effective (25,26,28,29). The Stx phage induced from the Norwegian O103:H25 isolate was shown to be capable of lysogeny after storage in a dry-fermented sausage model (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, the transduction of stx genes could lead to the emergence of new pathogenic clones that have not yet been described. Among multiple examples of bacterial conversion by Stx phages in vivo and in vitro (16,(25)(26)(27)(28)(29), the STEC O104:H4 strain that caused the huge outbreak of HUS in Germany in May 2011, and that also affected France, is the most recent case (30,31). The German O104:H4 strain presumably acquired the Stx phage in a late evolutionary event, generating a highly virulent pathogen that, unlike other enteroaggregative E. coli strains, produced the Shiga toxin (32).…”
Section: Discussionmentioning
confidence: 99%
“…The Stx2-encoding bacteriophage ⌽731 (⌬stx 2 ::cat) (hereinafter called ⌽731) was inserted into the chromosome of E. coli isolates and confirmed to be stable and functioning, as described previously (20). The original bacteriophage was carried by an E. coli O103:H25 strain from a Norwegian HUS patient (25).…”
Section: Methodsmentioning
confidence: 99%
“…A correlation between biofilm-forming abilities and persistence in food and feed-producing facilities has been reported for Salmonella enterica (18) and Listeria monocytogenes (19), and it has been suggested that biofilms in food-producing environments may serve as reservoirs for bacteria that may contaminate the food products. Furthermore, we have previously shown that dissemination of virulence genes like stx can occur in E. coli biofilm (20). Consequently, biofilms can also be environments for the evolution of new pathogenic E. coli isolates.…”
mentioning
confidence: 99%
“…Some studies have shown that transmission of stx phages may occur in water (Imamovic et al, 2009), in various food matrices (e.g. milk, orange juice, salad and ground beef) (Imamovic et al, 2009;Picozzi et al, 2012) and also in biofilms (Solheim et al, 2013).…”
Section: Dissemination Of Stx Phages Outside the Intestinementioning
confidence: 99%